Countering Political Misinformation in the US through Instructional Media Literacy: A Policy and Design Perspective - Yinka Samuel Ogunlana; Agama Omachi (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Media literacy has become an essential tool for addressing the growing challenges of misinformation, disinformation, and political propaganda in the digital age. This study explores the theoretical, pedagogical, and policy dimensions of media literacy as a framework for strengthening democratic integrity and civic engagement. It begins by examining historical patterns of propaganda, the role of social media in amplifying false information, and case studies of misinformation during elections and crises. The analysis then turns to education, highlighting curriculum design, pedagogical strategies for critical thinking and fact-checking, and the roles of teachers, librarians, and civic organizations in fostering informed citizenship. At the policy level, federal and state initiatives, regulatory practices, and the delicate balance between free speech and information integrity are critically assessed. Furthermore, the study investigates instructional design models, technology-enhanced learning tools such as games and AI, and evaluation metrics for program effectiveness. Finally, it emphasizes integrating media literacy into national education standards, advancing policy recommendations, and applying design thinking innovations to counter misinformation. Overall, the paper underscores the importance of a multidimensional approach that blends education, policy, and technology to safeguard democratic values in an era of information disorder.